DD-003 Implementation of an automated dispensing cabinet linked to an electronic prescribing programme in a home care service. (25th February 2017) - Lizardi, A; Ripa, C; Ercilla, M; Gayán, MJ; Odriozola, B; López, G; Lombera, L; Zurutuza, A; Urretavizcaya, M; García, D
Abstract : Background: Before October 2015, the dispensing procedure in the Home Care Service (HCS) was manual where medication for each patient was sent from the pharmacy service (PS) weekly in an individual bag. This procedure required high economic, time and human resources. For any treatment start or change, an individual order was requested as a pro re nata (PRN) medicine. Occasionally a global return of accumulated drugs was made. Purpose: In October 2015, the PS implemented an automated dispensing cabinet linked to an electronic prescribing programme (ADCLEP), Omnicell, in the HCS. PS replaced drugs automatically 2 days a week and staff from HCS placed them into the ADCLEP. The aim of this study was to evaluate the consequences of such implementation in the dispensing procedure evaluating the economic, time and human resources. Material and methods: Data were obtained from our electronic prescribing programme e-Osabide and our management computer programme SAP. A comparison between a period of 2 months (from 1 January to 29 February) was made in 2015 and 2016. The items registered were: number of PRN medicines; economic cost (€); and dispensing time and staff resources Results: Conclusion: The number of PRN medicines decreased by79%, dispensing time by 67%, dispensing staff resources by 67% and economic cost by 20%. Eliminating individual preparation and minimising the number of PRNs have had a great impact on PS care work. The main reason why the number of PRNs decreased is that the ADCLEP contains most of the medicines used by HCS. Economic cost was reduced due to more accurate and better adaptation to the patient's needs. Even though it has not been measured, prescriptions were updated more accurately and this could have led to less medication errors. Other advantages detected were no delay in the disposition of medicines and improvement in control of narcotics (book is generated automatically). We had no way of measuring the number of returns but the perception was that they decreased to almost none. ADCLEP is an efficient system and could be exported to other services. No conflict of interest